A matter of tolerance: Distribution potential of scyphozoan polyps in a changing environment. (21st October 2017) - Goldstein, Josephine; Augustin, Christina B.; Bleich, Steffen; Holst, Sabine
Abstract: Jellyfish blooms are unpredictable, unsustainable events, frequently affecting aquatic ecosystems severely. Of particular interest are the consequences of environmental change for jellyfish populations, especially in semi‐enclosed habitats. Regional and seasonal changes in water chemistry and physics may control the distribution of sessile polyps in the Baltic Sea, hence potentially driving the population dynamics of the two abundant medusa species Aurelia aurita and Cyanea capillata (Scyphozoa, Cnidaria). In laboratory experiments, settlement, growth, survival and physiological condition of A. aurita polyps were investigated at different levels of water temperature, pH and salinity. Survival and physiological condition of C. capillata polyps were examined after exposure to low salinity levels. Increased settlement of A. aurita planula larvae was observed on substrate plates at low temperature (4°C), low pH (7.4) and low salinity (7.5 psu), whereas early polyp growth was constrained by salinity ≤10 psu. Aurelia aurita polyps were in good physiological condition over the whole temperature range, while exposure to pH <6.5 led to stepwise tissue degradation. Salinity reduction to ≤5 and ≤8 psu caused irreversible degeneration of A. aurita and C. capillata polyps, respectively. Observed physiological limits suggest distribution of polyp populations of A. aurita in central and of C. capillata in western parts of the Baltic Sea, while future climate changes may particularly restrict occurrence of the less tolerant C. capillata .